2017
DOI: 10.1001/jamainternmed.2016.9607
|View full text |Cite|
|
Sign up to set email alerts
|

Thiazolidinediones and Advanced Liver Fibrosis in Nonalcoholic Steatohepatitis

Abstract: IMPORTANCE Nonalcoholic steatohepatitis (NASH) is projected to be the leading cause of liver transplantation by 2020. Advanced fibrosis (stage F3-F4) on liver biopsy independently predicts all-cause and liver-related mortality in NASH. There are no known efficacious treatments for advanced fibrosis related to NASH. Thiazolidinedione therapy has been extensively evaluated in NASH, and new randomized clinical trials (RCTs) of its efficacy have been completed.OBJECTIVE To synthesize the evidence about the associa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
272
0
12

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 368 publications
(288 citation statements)
references
References 29 publications
4
272
0
12
Order By: Relevance
“…Thirty male or female patients between the ages of 18 and 60 (Table S1 and S2) were randomized to: 1) twice daily 200 mg dose of MK-4074; 2) once daily 30 mg doses of pioglitazone; or 3) placebo for 4 weeks. A pioglitazone arm was included as a comparator since it has previously been shown to reduce liver TGs and fibrosis (Bajaj et al, 2003; Belfort et al, 2006; Cusi et al, 2016; Musso et al, 2017; Promrat et al, 2004; Sanyal et al, 2010). Hepatic fat content was assessed using magnetic resonance imaging (MRI) prior to first administration and following 4 weeks of treatment.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Thirty male or female patients between the ages of 18 and 60 (Table S1 and S2) were randomized to: 1) twice daily 200 mg dose of MK-4074; 2) once daily 30 mg doses of pioglitazone; or 3) placebo for 4 weeks. A pioglitazone arm was included as a comparator since it has previously been shown to reduce liver TGs and fibrosis (Bajaj et al, 2003; Belfort et al, 2006; Cusi et al, 2016; Musso et al, 2017; Promrat et al, 2004; Sanyal et al, 2010). Hepatic fat content was assessed using magnetic resonance imaging (MRI) prior to first administration and following 4 weeks of treatment.…”
Section: Resultsmentioning
confidence: 99%
“…Several studies have demonstrated a significant reduction in liver fat following the administration of pioglitazone (Bajaj et al, 2003; Belfort et al, 2006; Cusi et al, 2016; Musso et al, 2017; Promrat et al, 2004; Sanyal et al, 2010). Pioglitazone increases insulin sensitivity, which reduces activation of SREBP-1c and subsequently lowers rates of lipogenesis in liver (Araujo et al, 2016; Bell et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Fifty‐one percent of patients that received pioglitazone 45 mg daily for 72 weeks had resolution of NASH and improvement in several histologic features, including liver fibrosis. Finally, a meta‐analysis of five clinical trials that evaluated the use of pioglitazone for NASH showed significant improvement in advanced fibrosis even in patients without diabetes 21. Pioglitazone as a treatment for NASH should be used with caution due to several safety concerns, including weight gain and potential risk for congestive heart failure, bone fractures, and bladder cancer.…”
Section: Nafld/nash‐specific Therapiesmentioning
confidence: 99%
“…Two strategies directly aiming at preventing and reducing fibrosis in NASH are in clinical development with the caspase inhibitor emricasan in phase IIa and galectin 3 inhibitors in phase I [228,229,[232][233][234]. Although there is also some limited evidence that PPARγ activation itself might have anti-fibrotic activity [235], combination of anti-fibrotic approaches with PPAR agonists holds therapeutic promise. By preventing apoptosis of hepatocytes and reducing the formation of fibrotic tissue, caspase inhibitors or galectin 3 inhibitors could protect the liver architecture and retain hepatic function which might also result in synergistic efficacy Beyond combining agents to improve metabolic balance with direct anti-inflammatory or anti-fibrotic mechanisms also targeting metabolic anti-NASH effects in different tissues holds promise for synergistic activity.…”
Section: Dual Ppar Agonists Clinical Trialsmentioning
confidence: 99%